Deferasirox induces cyclin D1 degradation and apoptosis in mantle cell lymphoma in a reactive oxygen species‐ and GSK3β‐dependent mechanism. (31st January 2021) - Samara, Aladin; Shapira, Saar; Lubin, Ido; Shpilberg, Ofer; Avigad, Smadar; Granot, Galit; Raanani, Pia
Summary: Mantle cell lymphoma (MCL) is a difficult‐to‐treat B‐cell malignancy characterized by cyclin D1 (CD1) overexpression. Targeting CD1 in MCL has been shown to be of therapeutic significance. However, treatment of MCL remains challenging since patients are still subject to early and frequent relapse of the disease. To ensure their high proliferation rate, tumour cells have increased iron needs, making them more susceptible to iron deprivation. Indeed, several iron chelators proved to be effective anti‐cancer agents. In this study, we demonstrate that the clinically approved iron chelator deferasirox (DFX) exerts an anti‐tumoural effect in MCL cell lines and patient cells. The exposure of MCL cells to clinically feasible concentrations of DFX resulted in growth inhibition, cell cycle arrest and induction of apoptosis. We show that DFX unfolds its cytotoxic effect by a rapid induction of reactive oxygen species (ROS) that leads to oxidative stress and severe DNA damage and by triggering CD1 proteolysis in a mechanism that requires its phosphorylation on T286 by glycogen synthase kinase‐3β (GSK3β). Moreover, we demonstrate that DFX mediates CD1 proteolysis by repressing the phosphatidylinositol 3‐kinase (PI3K)/AKT/GSK3β pathway via ROS generation. Our data suggest DFX as a potential therapeutic option for MCL and paves the way for more treatment options for these patients.